2019
DOI: 10.3390/f10020101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Genetic Structure Inferred with Microsatellites in Natural Populations of Pseudotsuga menziesii (Mirb.) Franco (Pinaceae) in the Central Region of Mexico

Abstract: The amount and structure of the genetic diversity in Mexican populations of Pseudotsuga menziesii (Mirb.) Franco, is almost unknown, since most genetic studies have been carried out on populations from Canada and the United States. Here, we applied a set of 12 microsatellite markers to 12 populations (234 trees) from the central region of Mexico in order to determine values of genetic diversity and differentiation. Seventy-three different alleles were identified: an average number of alleles per locus (Na) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…More significant genetic variation within the population (88.2%) was also observed in Prosopis cineraria compared to the variance between populations (11.8%) (Sharma et al 2011). Similar results were also observed in the Pseudotsuga menziesii population, with diversity values of 72,2% within and 27.8% between populations (Castelan et al 2019). In contrast, in Tecomella undulata the diversity within populations was 64% and 36% among populations (Chhajer et al 2018).…”
Section: Genetic Distance Among Rosewood Population and Individuals I...supporting
confidence: 73%
“…More significant genetic variation within the population (88.2%) was also observed in Prosopis cineraria compared to the variance between populations (11.8%) (Sharma et al 2011). Similar results were also observed in the Pseudotsuga menziesii population, with diversity values of 72,2% within and 27.8% between populations (Castelan et al 2019). In contrast, in Tecomella undulata the diversity within populations was 64% and 36% among populations (Chhajer et al 2018).…”
Section: Genetic Distance Among Rosewood Population and Individuals I...supporting
confidence: 73%
“…In fact, it has been reported that high levels of genetic diversity are associated with high disturbance. Genetic diversity is closely related to the adaptive capacity of a species and guarantees, both to the individual and to the progeny, the possibility to better adapt when the ecological conditions are less stable and the evolutionary pressures more intense [70].…”
Section: Discussionmentioning
confidence: 99%
“…The structure and levels of genetic diversity of Mexican populations of P. menziesii is still unknown. Some studies suggest the prevalence of reduced sizes, a restricted distribution of populations and other factors that increase inbreeding (Montiel Castelán et al, 2019) and reduced level of diversity, especially in populations in the central region of Mexico (Cruz-Nicolás et al, 2011). This is related to the reduction in seed production, germination problems and initial growth (Ventura Ríos et al, 2010).…”
Section: Introductionmentioning
confidence: 99%